A Diagnostic Survey for Screening Patients for Post-Covid Conditions - Jacobs LG; Gourna Paleoudis E (International Journal of General Medicine, 2022)
Laurie G Jacobs,1 Elli Gourna Paleoudis2 1Department of Medicine, Hackensack Meridian School of Medicine, Nutley, NJ, USA; 2Department of Medical Sciences, Hackensack Meridian School of Medicine, Nutley, NJ, USACorrespondence: Laurie G Jacobs, Hackensack University Medical Center, 30 Prospect Avenue, Hackensack, NJ, 07601, USA, Tel +1 551 996 3500, Fax +1 551 996 3298, Email Laurie.Jacobs@hmhn.org